INCREASE INTEREST VISITING TOURISM IN KUNINGAN REGENCY - Wachjuni, Wachjuni; Mahsyar, Januar Habibi; Oktaviani, Winda (Jurnal Ilmiah Ekonomi Bisnis, 2024)
Kuningan is a beautiful mountainous area and a tourist destination from various regions in Indonesia and abroad. One of the managers of tourist attractions in Kuningan Regency is the Regional Company of Various Businesses (PDAU). However, the number of visitors from time to time has decreased. This research was conducted to determine people's interest in visiting tourist attractions managed by PDAU. The number of respondents used in this study was 150 people. This research is descriptive quantitative using SEM (Structural Equation Modeling) operated through the AMOS program. The results of direct influence research that advertising and innovation partially and significantly affect competitive advantage. Advertising, innovation and competitive advantage partially and significantly affect visiting interest. Indirect testing that advertising on visiting interest through competitive advantage variables has an effect. Innovation on visiting interest through competitive advantage variables has an effect. The implication of this research is as a reference and input so that PDAU conducts promotions through regular advertising and collaborates with related parties and makes updates/ innovations to tourist attraction facilities according to the needs of the community so that they become superior to other tourist attractions so as to increase visiting interest.